Optimisation of a Modified Solid-phase Microextration Method for the Analysis of Alklphenols in Water Samples - 박현미; 이강봉; Soon-Min Hong (한국환경분석학회, 2005)
Optimization of solid-phase microextraction(SPME) for the analysis of alkylphenols(4-t-butyl, 4-n-butyl, 4- n-hexyl, 4-n-heptyl, 4-t-octyl, nonyl) and bisphenol-A in water samples were investigated. Polyacrylate(PA) fiber was modified with silylating reagent Bis(trimethylsilyl)trifluoroacetamide (BSTFA)/ Trimethylcholro silane(TMCS)(100:1 v/v) before extraction. After extraction, the modified PA fiber was directly transferred to the injector of a gas chromatograph where the analytes are thermally desorbed and subsequently separated and quantified. Extraction parameters such as extraction time, pH of sample, concentration of salt added were optimised. The proposed method provided a good reproducibility less than 15%, and good linearity(R>0.9). Limits of detection(LODs) ranged between 0.2 and 1.7 μg/L and were almost equivalent to those by liquid-liquid extraction (LLE) (0.1~1.0 μg/L). The results obtained suggested that modified SPME was a rapid, simple and efficient technique for the analysis of alkylphenols and bisphenol A in water sample and it can simultaneously do derivatization and extraction. The formation of trimethylsilyl derivatives improves the selectivity, sensitivity and performance of the chromatographic properties.